USE OF NATURAL LATEX LIQUID FOR FABRICS INTERLINING - Luftinor Luftinor (Balai Riset dan Standardisasi Industri Palembang, 2017)
Latex natural liquids as raw materials plus other chemicals such as ZDEC, ZMBT, Ionol, ZnO, Sulfur and kaolin have been used as coatings on Interlining fabrics, ie fabrics used to coat certain parts of clothing such as collar, waist, buttons, the tip of the arm, the shoulders of the suit and other parts that require high stiffness and a stable shape to beautify the apparel appearance. The research was conducted by making 4 formula of natural latex compound liquid by varying Kaolin filler in 4 levels, ie 90 g, 180 g, 270 g and 360 g and varying temperature on drying process each 80°C, 100°C, 120°C dan 140°C. The parameters tested were fabric rigidity, adhesive strength, tensile strength, stretching and tear strength. The objective of the study was to obtain the right natural liquid latex compound formula as a coating material in the manufacture of interlining fabrics having specifications in accordance with the SNI 0894-2008 standard. Natural latex can be used as a coating material on the manufacture of hard interlining fabrics, the increased use of kaolin fillers to a certain extent on the manufacture of latex compounds can improve the physical properties of fabric rigidity, but decrease the physical properties of adhesive strength, tensile strength, tear and tear strength of interlining fabric. Increasing the temperature in the drying process to some extent can improve the physical properties of fabric rigidity, adhesive strength, tensile strength, stretching and tear strength of interlining fabric. The best results were obtained on the formula III of drying temperature of 120°C, obtaining fabric stiffness value of 90.62 mg.cm, adhesion strength 1.24 kg/cm, tensile strength 34.43 kg for the direction of warp and 26,20 kg for feed direction, 35,43% for direction of warp and 31,62% for feed direction, tear strength 3,48 kg for direction of warp and 3,45 kg for feed direction